Kesenian Kuda Lumping Sanggar New Suryo Budoyo Dikecamatan Lahat Kabupaten Lahat - Azizah Nurul Khasanah; Dedy Firmansyah; Ahmad Heryanto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
In accordance with the phenomena in the field, the background to this thesis is the Kuda Lumping art which has developed in the Sumatra region, specifically the transmigration region, because the majority of people there are people from the Java region. The Kuda Lumping dance originates from East Java and is inspired by the story of the Kediri Kingdom. The Kuda Lumping dance art has one characteristic property, namely that in the dance it uses props made of woven bamboo. This writing uses qualitative methods. The data collection process in this writing uses observation, interviews, documentation methods. Based on the results of research that has been carried out using qualitative methods, it is descriptive about Kuda Lumping art, make-up and clothing for Kuda Lumping, and Kuda Lumping music.